Türkiye’de lisans düzeyinde çalgı eğitiminin verildiği müzik okullarındaki ney eğitiminin, öğretim elemanlarının görüşlerine göre değerlendirilmesi - Berse, İdris Melih (My University, 2018)
Bu araştırma, Türkiye’de lisans düzeyinde ney eğitimi veren öğretim elemanlarının görüşlerine göre, lisans düzeyinde çalgı eğitiminin verildiği müzik okullarındaki ney eğitiminin değerlendirilmesi amacıyla yapılmıştır. Araştırma kapsamında gerekli verilerin elde edilmesi amacıyla, örneklem alanını oluşturan Türkiye’deki müzik okullarında 2016 yılı itibariyle ney alanında görev yapmakta olan 16 öğretim elemanına 57 sorudan oluşan bir anket uygulanmıştır. Anket yapılan öğretim elemanlarının verdikleri cevaplardan hareketle elde edilen bulgular, tablo ve grafik halinde gösterilerek sonuçlar analiz edilmiş, değerlendirme yapılmıştır. Araştırmada elde edilen sonuçların, ney eğitimcilerine yol göstereceği ve bu konuda yapılacak olan diğer çalışmalara ışık tutacağı düşünülmektedir.

This research was conducted to evaluate the Ney training according to faculty members’ view in the music schools where the undergraduate level musical instrument training is given in Turkey. A survey consisting of 57 questions was applied to 16 faculty members, who was already working 2016, in the musical schools which constitute the sampling area in order to obtain the necessary data for the research. The findings obtained from the survey which applied to faculty members were shown in tables and figures and the results were analyzed accordingly. It is thought that the results obtained in the study will lead to the Ney instructors and future studies in this field.
Keywords: A survey consisting of 57 questions was applied to 16 faculty members; Dini yönleri; Eğitim ve çalışma; Instruction and study; Islam; Islamic music; It is thought that the results obtained in the study will lead to the Ney instructors and future studies in this field; in the musical schools which constitute the sampling area in order to obtain the necessary data for the research; İslam; İslami müzik; Methods; Metotlar; Music; Müzik; Nāy; Ney; Ney Eğitimi This research was conducted to evaluate the Ney training according to faculty members’ view in the music schools where the undergraduate level musical instrument training is given in Turkey; Neyzen; Religious aspects; The findings obtained from the survey which applied to faculty members were shown in tables and figures and the results were analyzed accordingly; Turkey; Türkiye; who was already working 2016